Meso‐to‐meso Sulfide‐ and Disulfide‐Bridged Subporphyrin Dimers. Issue 11 (5th April 2016) - Copley, Graeme; Shimizu, Daiki; Oh, Juwon; Sung, Jooyoung; Furukawa, Ko; Kim, Dongho; Osuka, Atsuhiro
Abstract: Treatment of meso ‐chlorosubporphyrin with controlled equivalents of Na2 S· 9H2 O in DMF led to the formation of either meso ‐to‐ meso sulfide (S)‐bridged dimer4 or disulfide (SS)‐bridged subporphyrin dimer6 . S‐bridged dimer4 displayed a split Soret‐like band and a large Stokes shift and became a fully delocalized one‐quantum system in the S1 state, as indicated by femtosecond transient absorption anisotropy measurements and theoretical calculations. Contrastingly, SS‐bridged dimer6 showed a broad but nonsplit Soret‐like band, no fluorescence, and very fast S1 decay with a lifetime of 4 ps, which indicated the presence of a rapid decay channel. Abstract : meso ‐to‐ meso S‐bridged and SS‐bridged dimers4 and6 are prepared by SN Ar reaction of meso ‐chlorosubporphyrin. Dimer4 displays a split Soret‐like band and a large Stokes shift, whereas dimer6 shows weaker interchromophoric interaction. Dimer4 becomes a one‐quantum system in the S1 state, whereas the S1 state of6 displays very fast decay to the ground state with a lifetime of 4 ps.